GASTRIC ULCER PENETRATING TO THE DUODENOJEJUNAL FLEXURE - MANAGEMENT AND PITFALLS. CASE REPORT AND REVIEW OF THE LITERATURE - Georgi Popivanov; Alexander Kacarov; Marina Konaktchieva; Roberto Cirocchi; Tsvetelina Paycheva; Marin Penkov; Kirien Kjossev; Ventsislav Mutafchiyski (Peytchinski Publishing, 2022)
Introduction: The penetration into adjacent organs is a classical complication of peptic ulcer despite being less frequent than the other complications. The current work presents a rare case of gastric ulcer penetrating the duodenojejunal flexure and discusses the diagnostic difficulties, pitfalls, and current treatment strategy. Case report: A 63-years-old woman was admitted complaining of intermittent black stools defecations, and a weight of 44 kg. The referral gastroscopy revealed a 10 cm ulcer on the posterior wall of the stomach. The histology demonstrated severe gastritis with atypical cells. The hemoglobin level was 88g/l. The patient was scheduled for elective resection for suspected gastric cancer. The intraoperative finding was completely different - there was an ulcer approximately 4-5 cm in diameter infiltrating the transverse mesocolon and duodenojejunal flexure. The case was considered T4 cancer and we decided against elective gastrectomy. The postoperative CT showed an ulcer penetrating the duodenojejunal flexure. The second gastroscopy found an ulcer with a size of 3-4 cm. The multiple biopsies showed exacerbated chronic peptic ulcer with H. pylori infection, which was treated with proton pump inhibitors and antibiotics. The follow-up gastroscopy four months later demonstrated shrinkage of the ulcer to 15 mm with complete epithelization. One year later she gained 23 kg and was free of complaints. Conclusion: Penetration and fistulization to the duodenojejunal flexure are uncommon but possible complications of peptic ulcer disease. They are not an absolute indication for surgery. Decision-making should take into account the clinical presentation, patient age, and comorbidity.